SISTEM PAKAR MENDETEKSI TINDAK PIDANA CYBERCRIME MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB DI KOTA BATAM - Putri, M.Kom, Anggia Dasa (STKIP PGRI Sumatera Barat, 2017)
Advances in information technology provides much convenience for human life, but even this progress simultaneously cause a variety of problems that are not easy to find a way out. One of the problems arising from the development of information technology, namely the birth of crimes that refers to activities undertaken in the virtual world using a computer or computer network technology, known as cybercrime (cybercrime). Crime cybercrime common daily life such Decency, Gambling, humiliation or defamation, extortion or threatening, Spreading false news, Abuse, Hacker, Cracker, falsification of data, due to internet users, or lack of awareness about the Law Number 11 Year 2008 Information and Electronic Transaction applicable. Therefore, this study aims to develop an expert system using programming language PHP (Hypertext Preprocessor) and MySQL database-based web using a forward chaining method to make it easier, knowing, and assist in taking an answer or conclusion of cases and sanctions crime cyberspace (cybercrime) based on Law No. 11 of 2008 on Information and Electronic Transactions applicable.